2019
DOI: 10.1021/acs.langmuir.8b03478
|View full text |Cite
|
Sign up to set email alerts
|

Spreading Films of Anthracene-Containing Gelator Molecules at the Air/Water Interface: Nanorod and Circularly Polarized Luminescence

Abstract: Two enantiomeric gelator molecules containing anthracene moiety were assembled at the air/water interface and several new insights into the films of the gelator molecules were revealed. When these molecules were spread at the air/water interface, they formed the nanorod structured monolayers and could be subsequently transferred to the solid substrate. The formed Langmuir–Blodgett (LB) films showed both optical activity and circularly polarized luminescence (CPL) due to the chirality transfer upon assembling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…For instance, nanorod structured monolayers were fabricated at the air/water interface using an LB technique with the self‐assembly of two enantiomeric gelator molecules containing an anthracene moiety. [ 71 ] During this process, chiral sense was transferred to the assemblies, enabling the LB films to demonstrate both optical activity and CPLU properties, as shown in Figure A. It was also found that the dissymmetric factors of the CPLU in the LB films were enhanced by nearly five times those in gel systems because of the more compact 2D stacking mode of molecules in LB films.…”
Section: Asymmetrical Self‐assembly At the Interfacementioning
confidence: 96%
See 2 more Smart Citations
“…For instance, nanorod structured monolayers were fabricated at the air/water interface using an LB technique with the self‐assembly of two enantiomeric gelator molecules containing an anthracene moiety. [ 71 ] During this process, chiral sense was transferred to the assemblies, enabling the LB films to demonstrate both optical activity and CPLU properties, as shown in Figure A. It was also found that the dissymmetric factors of the CPLU in the LB films were enhanced by nearly five times those in gel systems because of the more compact 2D stacking mode of molecules in LB films.…”
Section: Asymmetrical Self‐assembly At the Interfacementioning
confidence: 96%
“…Adapted with permission. [ 71 ] Copyright 2019, American Chemical Society. B) Dynamic control over supramolecular chirality at the solution–solid interface.…”
Section: Asymmetrical Self‐assembly At the Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the fabrication of the chiral supramolecular assemblies has been attracting much attention. There are many ways to fabricate a chiral supramolecular, such as self-assembly in solution, supramolecular gelation, and Langmuir–Blodgett (LB) technique. Owing to the fact that the LB technique can provide a prominent manner to regulate the molecular orientation and assemble in a two-dimensional (2D) mode at the gas/liquid interface. The LB technique is considered one of the available ways to fabricate 2D nanostructures. In general, classical amphiphiles with hydrophilic headgroups and long hydrophobic chains are most investigated to assemble into uniform monolayer by the LB technique.…”
Section: Introductionmentioning
confidence: 99%
“…However, as an interfacial assembly method, the LB or LS technique can be largely extended to various entities beyond amphiphiles. Various nanostructures such as nanotubes, , nanoparticles, , nanowires, , metal–organic frameworks (MOFs), 2D nanosheets, perovskites, and others were spread on the water surface to facilitate an array of nano-objects in a two-dimensional film. Previously, we have reported the formation of LB films and CPL from an anthracene-appended amphiphilic molecule . An enhancement of the luminescent dissymmetry factor ( g lum ) was observed in the LB films compared to those in gels.…”
Section: Introductionmentioning
confidence: 99%